1996
DOI: 10.1109/86.486051
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory assistance using electrical stimulation of abdominal muscles

Abstract: Nine neurologically intact subjects were studied to demonstrate the feasibility of stimulating the muscles of expiration during, and in synchrony with, naturally occurring breathing. A breath-by-breath analysis showed that both tidal volume and the frequency of respiration could be increased during periods of electrical stimulation. A single subject with complete spinal cord injury was studied to eliminate the possibility that the results from the normal subjects could be attributed entirely to either subconsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Ten studies investigated the acute effect of 6 Abdominal FES, [2][3][4][5][6][7][8][31][32][33] while four studies investigated the chronic effect of Abdominal FES training. 9,10,14,15 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies investigated the acute effect of 6 Abdominal FES, [2][3][4][5][6][7][8][31][32][33] while four studies investigated the chronic effect of Abdominal FES training. 9,10,14,15 …”
Section: Resultsmentioning
confidence: 99%
“…While not included in the meta-analysis due to a lack of data, three studies have reported that Abdominal FES led to a significant acute increase in Tidal Volume (VT) for participants with an SCI, 3,7,8 indicating that this measure may be worthy of further exploration. Kandare et al 31 also demonstrated that Abdominal FES could be used to support respiration for patients who lacked spontaneous ventilation, with the intervention able to provide an adequate VT for up to three and a half minutes.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…While the study reported in [23] focused on quiet breathing their system was not applicable for cough induction. On the other side, the study in [24] focused on a system to generate an automatic trigger for cough, but did not consider other breathing situations.…”
Section: A Overviewmentioning
confidence: 99%
“…This approach was used byŠorli et al [23] and Spivak et al [24] for specific respiratory situations. While the study reported in [23] focused on quiet breathing their system was not applicable for cough induction.…”
Section: A Overviewmentioning
confidence: 99%